Research progress and prospect of coal seam blasting antireflection technology in China - Zegong LIU; Guodong QIAO; Jian LIU; Kui GAO (Meitan xuebao)
The permeability enhancement technology in coal seam blasting has made significant contributions to the prevention and control of coal and gas outburst disasters in China. Extensive and in-depth research has been conducted on both the permeability enhancement mechanism and practical applications. To summarize past experiences and further enhance the technology for deep coal seam blasting in the new era, this study analyzes the blasting permeability enhancement mechanism, establishes a mathematical model for blasting-induced fracturing of coal-rock masses considering dynamic compressive (tensile) strength and ideal detonation conditions, and inversely examines stress distribution around blasting holes under different geological stress conditions. The development history and research progress of China’s coal seam blasting permeability enhancement technology are elucidated, and various types of technologies developed in recent decades are summarized. Innovative achievements have been made in theories and practices concerning the permeability enhancement mechanism and construction processes of coal seam blasting in China, resolving numerous theoretical and technical challenges. However, as coal mining in China shifts to deeper areas and geological conditions of coal mines become increasingly complex, new requirements are imposed on coal seam blasting permeability enhancement technology. Therefore, future development trends and prospects of coal seam blasting permeability enhancement technology are proposed: in deep structural areas of coal seams, precise directional blasting technology should be developed to enhance permeability accurately while avoiding deep-seated secondary coal-rock dynamic disasters; for permeability enhancement in soft and low-permeability coal seams, traditional borehole layout techniques should be revised, and blasting holes should be constructed within roof and floor strata, promoting strata blasting permeability enhancement technology; in intelligent blasting permeability enhancement, integration with artificial intelligence and big data analysis methods should be pursued, focusing on intelligent design of blasting schemes and evaluation of blasting effects, thereby further advancing coal seam blasting permeability enhancement technology in alignment with China’s direction towards safe and intelligent coal mining development.